2000
DOI: 10.1093/oxfordjournals.jbchem.a022845
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Meltrin   Is Ubiquitously Expressed and Associated with the Plasma Membrane but Exogenous Meltrin   Is Retained in the Endoplasmic Reticulum

Abstract: Meltrin alpha (ADAM12) is a member of the ADAM (MDC) protein family characterized by the presence of metalloprotease and disintegrin domains. ADAM proteins contain single transmembrane domains, and the processed mature proteins are postulated to span the plasma membrane. It has been reported that transfection of a truncated meltrin alpha cDNA lacking the prodomain and metalloprotease domain promotes skeletal muscle cell fusion. We show here that meltrin alpha was constitutively expressed in both undifferentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…Although endogenous ADAM12 has been reported to be proteolytically processed and it has been found mainly in the plasma membrane (29,43), exogenous mouse ADAM12 has been claimed either to reside in the plasma membrane (44) or to be entirely retained in the ER, where it lacks any processing (43). In contrast, human ADAM12 expressed in COS-7 cells as a GFP fusion protein is confined exclusively to the trans-Golgi network and is subject to proteolytic processing (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although endogenous ADAM12 has been reported to be proteolytically processed and it has been found mainly in the plasma membrane (29,43), exogenous mouse ADAM12 has been claimed either to reside in the plasma membrane (44) or to be entirely retained in the ER, where it lacks any processing (43). In contrast, human ADAM12 expressed in COS-7 cells as a GFP fusion protein is confined exclusively to the trans-Golgi network and is subject to proteolytic processing (42).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the processed form of ADAM12-GFP is retained in the trans-Golgi network (TGN), with very little protein present at the cell surface (42). When overexpressed in C2C12 myoblasts or 10T1/2 fibroblasts, mouse ADAM12 does not undergo any proteolytic processing and localizes exclusively in the endoplasmic reticulum (ER) (43). In clear contrast, a mature form of ADAM12 is expressed at the cell surface of Chinese hamster ovary cells transfected with full-length mouse ADAM12, where it supports the interactions with integrin ␣ 9 -expressing cells (44).…”
mentioning
confidence: 99%
“…Northern blotting was carried out as stated elsewhere (Endo and Nadal-Ginard, 1987). Quantitative RT-PCR was performed as described previously (Kadota et al, 2000). The amplification reaction was conducted according to a step program (at 95°C for 60 seconds, at 58°C for 15 seconds and at 72°C for 60 seconds).…”
Section: Methodsmentioning
confidence: 99%
“…The primers used for RhoT amplification were the same as those used for the cloning. The primers for glyceraldehyde 3-phosphate dehydrogenase (GAPDH) as a control were as previously described (Kadota et al, 2000). After 50 and 17 cycles of amplification, respectively, these products were in the linear range.…”
Section: Methodsmentioning
confidence: 99%
“…Immunostaining of ADAM12 in mpc after plasma membrane permeabilization revealed both intracellular and plasma membrane localization of ADAM12 ( Figure 2C). Such a distribution in the murine myogenic cell line C2C12 (Cao et al, 2002) and other cell types (Hougaard et al, 2000;Kadota et al, 2000) has been shown to reflect association to the organelles composing the secretory pathway, i.e., endoplasmic reticulum, Golgi apparatus, and post-Golgi components. Moreover, plasma membrane labeling showed as discrete and elongated spots distributed throughout the cell body and plasma membrane projection as lamellipodiae (Hougaard et al, 2000;Kadota et al, 2000) ( Figure 2C).…”
Section: Human Mpc Constitutively Express Adam12 During In Vitro Myogmentioning
confidence: 96%